Methods and Techniques to Facilitate the Development of Clostridium novyi NT as an Effective, Therapeutic Oncolytic Bacteria - Dailey, Kaitlin M.; Jacobson, Reed I.; Johnson, Paige R.; Woolery, Taylor J.; Kim, Jiha; Jansen, Rick J.; Mallik, Sanku; Brooks, Amanda E. (Frontiers in Microbiology, 2021)
The tumor microenvironment is characterized by anomalous vascularization, hypoxia, and acidity at the core of solid tumors that culminates in concentrated necrosis and immune system dysregulation among other effects. While this environment presents several challenges for the development of oncotherapeutics that deliver their activity via the enhanced permeability and retention (EPR) effect of the leaky blood vessels around a tumor, oncolytic bacteria, or a class of bacteria with a noted capacity to lyse solid tumors, are attracted to the very environment found at the center of solid tumors that confounds other therapeutics. It is this capacity that allows for a potent, active penetration from the tumor margins into the core, and subsequent colonization to facilitate lysis and immune reactivation. Clostridium novyi in particular has recently shown great promise in preclinical and clinical trials when administered directly to the tumor. These studies indicate that C. novyi is uniquely poised to effectively accomplish the long sought after ‘holy grail’ of oncotherapeutics: selective tumor localization via intravenous delivery. This study reports the development of efficient methods that facilitate experimental work and therapeutic translation of C. novyi including the ability to work with this obligate micro-anaerobe aerobically on the benchtop. Additionally, this study seeks to utilize this newfound experimental flexibility to address several gaps in the current knowledge regarding the efficacy of CRIPSR/Cas9 gene insertion in this species to further develop this oncolytic bacteria and the genetic customization of bacteria in general.